Plant Diversity of an Andean Cloud Forest : Inventory of the Vascular Flora of Maquipucuna, Ecuador - Webster, Grady L. (Book collections on Project MUSE., 2001)
Based on work spanning a decade, this study of the Maquipucuna area on the western slopes of the Andes discusses the climate, vegetation, ecological relationships and flora, and emphasizes the importance of the Maquipucuna area as a biological reserve.